Factors Affecting Student Invest in The Capital Market Through the Investment Gallery of Maarif Hasyim Latif University – Sidoarjo - Adinda Rizky Maulidia; Darno Darno; Dewi Agustya Ningrum (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The Indonesia Stock Exchange is intensively conducting a campaign with the theme